Batch metal removal by peat. Kinetics and thermodynamics - Gosset, T.; Trancat, J.L.; Thevenot, D.R. (Water Research, 1986)
Peat moss, a natural inexpensive material, is able to play an important role in treatment processes of metal-bearing industrial effluents since it adsorbs, complexes or exchanges various metal cations. This paper presents kinetics and thermodynamics of batch metal removal reactions by 50 g l-1 (dry wt) eutrophic or oligotrophic peat particles using Cu2+, Cd2+, Zn2+ and Ni2+ concentrations ranging from 0.01 to 100 mM. Metal cation removal reactions are moderately rapid in 10 mM metal unbuffered solutions: the forward kinetic constant ranges between 0.005 and 0.17 M-1 s-1, and equilibrium is reached within about 1 h. Under these conditions of pH (2.2-4.2) and concentrations, apparent binding equilibrium constants were found to range between 2 and 3150 M-1 depending upon the peat origin and the metal cation. In 0-6.5 pH-buffered metal cation solutions, the four cations binding reactions behaved differently demonstrating that metal binding equilibrium constants decrease in the order Ni2+ > Cu2+ > Cd2+ = Zn2+. When pH is higher than 6.7, more than 90% of a 10 mM metal cation solution is removed by 50 g l-1 peat particles and metal binding capacities equal 200 mmol kg-1 dry wt, whatever the metal nature and the peat origin. Except for nickel cation which is very strongly bound to peat, all metal cations are completely released when pH is fixed below 1.5. Peat moss, a natural inexpensive material, is able to play an important role in treatment processes of metal-bearing industrial effluents since it adsorbs, complexes or exchanges various metal cations. This paper presents kinetics and thermodynamics of batch metal removal reactions by 50 g l minus 1 (dry wt) eutrophic or oligotrophic peat particles using Cu2 plus , Cd2 plus , Zn2 plus and Ni2 plus concentrations ranging from 0. 01 to 100 mM.